The Significance of Aesthetic and Heritage Values in a Public Policy Environment: Victoria Theatre Case Study - Milne, Lise (Auckland University of Technology, 2011)
This thesis explores the significance of aesthetic and heritage values through a case study; the Victoria Theatre in Devonport, Auckland, New Zealand. The research led me to question aesthetic philosophy, theory and experience. While analysing policy documents surrounding heritage values, reference was consistently made to "aesthetics". However there were no specific definitions provided for the meaning of the word "aesthetic". Aesthetic values, as is with heritage, are formed on subjective judgements. I began to question the role that „aesthetics‟ played in policy planning as the meaning was not clearly defined. My aim was to bring to light the aesthetic and understand how subjective aesthetic and heritage values were identified on which public policy decisions were made. A phenomenological approach to interviews uncovered subliminal heritage values found in aesthetic experiences. Even though key informants could not specifically explain the meaning of the word aesthetic, when it came to describing their passion and motivation for protection of a heritage theatre, a deep sense of the aesthetic values emerged. Common values between aesthetics and heritage were identified. Heritage became a conduit for describing the aesthetic experience. The lived experience of aesthetic and heritage values were identified.
Keywords: Aesthetic values; Heritage values; Public policy; Victoria Theatre